Associations of depression-anxiety and dyslipidaemia with subclinical carotid arterial disease: Findings from the Whitehall II Study. (May 2020) - Ellins, Elizabeth A; Shipley, Martin J; Rees, D Aled; Kemp, Andrew; Deanfield, John E; Brunner, Eric J; Halcox, Julian P
Aims: There is mixed evidence for an association between depression and/or anxiety and carotid intima-media thickness, and limited information on the related role of dyslipidaemia. Here we report associations between depression and/or anxiety and intima-media thickness in the Whitehall II cohort, considering the moderating effects of sex and dyslipidaemia. Methods: A total of 2822 men and 1112 women (61 ± 6 years) were studied during phase 7 (2002–2004) of the Whitehall II study. Intima-media thickness and lipid levels were assessed, and questionnaires (general health questionnaire and the Centre for Epidemiologic Studies depression scale) were completed. Linear regression was used to explore relationships between depression and/or anxiety and intima-media thickness and the moderating effects of sex and dyslipidaemia. Results: A total of 1461 participants were categorised with depression and/or anxiety. The association between depression and/or anxiety and intima-media thickness differed between men and women so analyses were undertaken separately by sex. In men, intima-media thickness was significantly associated with dyslipidaemia ( P  = 0.002) but not depression and/or anxiety ( P  = 0.29). In women, both dyslipidaemia and depression and/or anxiety were independently associated with intima-media thickness ( P  = 0.028 and P  = 0.031). The greatest intima-media thickness was in women with both depression and/or anxiety and dyslipidaemia. These results were replicated when the general health questionnaire score was substituted for depression and/or anxiety and non-high-density lipoprotein cholesterol for dyslipidaemia. Conclusions: Depression and/or anxiety is associated with increased intima-media thickness in women but not in men. Dyslipidaemia is associated with intima-media thickness in both men and women. Women with both depression and/or anxiety and dyslipidaemia are potentially at the greatest risk of cardiovascular disease.